الرقابة المالية على الاستثمارات الخاصة في القانون الجزائري (مجلة الواحات للبحوث والدراسات, 2021)
It Is Agreed That Investment Is The Key To Development. So, The Algerian Legislator Adopted It By Setting Rules That Ensure Facilities And, Benefits And Guaranties. This Encourages Local Investment And Attracts Foreign One Order To Improve The Economy And Create Job Opportunities.At The Same Time, The Algerian Legislator Has Dedicated In His Law System Related To Investment, A Control System On Invested Capitals From The Beginning Of The Project Foundation Till To Its End And Also The Transfer Of Funds Abroad.This Document Provides Information (Details) About The Way Of Controlling Invested Capital And To What Extent It Is Efficient In Protecting The National Economy. Keywords–  Investment, Capital,  Authorization,  Pre-Emption Right ,  Exchange Control,  National Agency Of Investment Development , National Investment Board.